Private health insurance as a source of financing the healthcare system in Poland - Jacek Rodzinka; Małgorzata Paszkowska (e-Finanse: Financial Internet Quarterly, 2013)
The medical services market in Poland is financed mainly with funds from national health insurance, yet year by year, an increasing importance of private resources in financing health services can be noticed. Apart from common (national) health insurance, medical care is primarily financed directly by the patient and possibly by his employer (occupational medicine, additional private medical care). The purpose of this paper is to present the basic legal and market aspects of private health insurance in Poland, including a presentation of the structure of private healthcare expenses in Poland.
Keywords: I11; I15; I18; 330; Poland; health care; financing system